Vietnam and Indonesia daily climate data (precipitation and temperature) per sub-geographical units 2000-2018 - Achicanoy Estrella, Harold Armando; Mora, Brayan; Ramírez Villegas, Julián Armando; Prager, Steven D. (International Center for Tropical Agriculture, 2020)
Daily climate data (precipitation and temperature) for Vietnam and Indonesia per sub-geographical units during the period 2000-2018